Optimalisasi Aplikasi Berbasis Web dalam Upaya Promosi dan Peningkatan Tingkat Hunian Kamar pada Santika Premiere Dyandra Hotel & Convention Medan - Liyushiana Liyushiana (Politeknik Pariwisata Medan, 2022)
Hotels play an important role in the tourism industry. Without a hotel, tourists would not be able to enjoy a comfortable vacation. This is because the hotel provides the services and other services you need for a comfortable stay. The hotel itself has the concept of a type of accommodation that is commercially operated, providing services such as accommodation, services and food and drink to the general public for a short stay. Medan has so many Star Hotel competitors that you need to develop an appropriate marketing strategy. Therefore, the right marketing strategy applicable in today's digital age is digital marketing, especially web-based applications. In this case, Hotel Santika Premiere Dyandra Medan also digitally marketed web-based applications and more. This is one of the mainstays for promoting and increasing room occupancy, which has been sluggish in recent years due to the Covid 19 pandemic. Web-based applications are called MySantika and MyValue. The benefits of the Internet and digital marketing are so great that you can benefit from the Internet in almost every area, including: B. Business sector through banking, insurance, travel, education, etc. Since the advent of the Internet, patterns of daily life have gradually changed.